Advantages of Revision Transforaminal Full-Endoscopic Spine Surgery in Patients who have Previously Undergone Posterior Spine Surgery - Yagi, Kiyoshi; Kishima, Kazuya; Tezuka, Fumitake; Morimoto, Masatoshi; Yamashita, Kazuta; Takata, Yoichiro; Sakai, Toshinori; Maeda, Toru; Sairyo, Koichi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Revision lumbar spine surgery via a posterior approach is more challenging than primary surgery because of epidural or perineural scar tissue. It demands more extensive removal of the posterior structures to confirm intact bony landmarks and could cause iatrogenic instability; therefore, fusion surgery is often added. However, adjacent segment disease after fusion surgery could be a problem, and further exposure of the posterior muscles could result in multiple operated back syndrome. To address these problems, we now perform transforaminal full-endoscopic spine surgery (TF-FES) as revision surgery in patients who have previously undergone posterior lumbar surgery. There have been several reports on the advantages of TF-FES, which include feasibility of local anesthesia, minimal invasiveness to posterior structures, and less scar tissue with fewer adhesions. In this study, we aim to assess the clinical outcomes of revision TF-FES and its advantages.Methods We evaluated 48 consecutive patients with a history of posterior lumbar spine surgery who underwent revision TF-FES (at 60 levels) under local anesthesia. Intraoperative blood loss, operating time, and complication rate were evaluated. Postoperative outcomes were assessed using the modified Macnab criteria and visual analog scale (VAS) scores for leg pain, back pain, and leg numbness. We also compared the outcome of revision FES with that of primary FES.Results Mean operating time was 70.5 ± 14.4 (52–106) minutes. Blood loss was unmeasurable. The clinical outcomes were rated as excellent at 16 levels (26.7%), good at 28 (46.7%), fair at 10 (16.7%), and poor at 6 (10.0%). The mean preoperative VAS score was 6.0 ± 2.6 for back pain, 6.8 ± 2.4 for leg pain, and 6.3 ± 2.8 for leg numbness. At the final follow-up, the mean postoperative VAS scores for leg pain, back pain, and leg numbness were 4.3 ± 2.5, 3.8 ± 2.6, and 4.6 ± 3.2, respectively. VAS scores for all three parameters were significantly improved (p < 0.05). There was no significant difference in operating time, intraoperative blood loss, or the complication rate between revision FES and primary FES.Conclusions Clinical outcomes of revision TF-FES in patients with a history of posterior lumbar spine surgery were acceptable (excellent and good in 73.4% of cases). TF-FES can preserve the posterior structures and avoid scar tissue and adhesions. Therefore, TF-FES could be an effective procedure for patients who have previously undergone posterior lumbar spine surgery.
Keywords: revision lumbar spine surgery; transforaminal full-endoscopic spine surgery; adjacent segment disease; minimally invasive surgery; multiple operated back syndrome; complication